Is blood donation an opportunity for hypertension awareness?. Issue 2 (21st March 2016) - Hao, J.; McAvoy, J.; Wickberg, L.; Kerrigan, C.; Kreiger, L.; Sikavi, C.; Swift, D.; Frenette, C.; Carney, J.; Fung, M. K.
SUMMARY: Objectives: To assess the blood pressure (BP) of donors, the rate of hypertensive range readings amongst donors not previously identified as hypertensive and determine the value of an informational sheet about hypertension given at the time of donation. Aim: To determine the value of screening for high BP during blood donation as a public health activity. Background: Blood donation centres measure donor BPs before accepting donations and thus provide a unique opportunity for hypertension screening and education. Materials/methods: An anonymous survey was completed by blood donors over 2 weeks. The survey contained 22 questions regarding demographics, BP knowledge and monitoring. Participants then received a hypertension information sheet and assessed its utility with three additional questions. Results: Out of 839 survey responses received, 688 respondents reported their BP in the following categories, normotensive range: 46·9%, pre‐hypertensive range: 41·7% and hypertensive range: 11·3%. Notably, of donors with hypertensive range readings, 45% reported no known history of hypertension. After reading the hypertension pamphlet, 63·9% of donors found it valuable, while 38·9% did not. Furthermore, 67% of donors said they were likely to use the information they learned, while 23% of donors said they were unlikely to do so. Conclusions: An opportunity exists for increasing hypertension awareness during blood donation. Additionally, our findings indicate that an educational pamphlet at the time of donation is valuable to donors. Overall, these findings suggest that increasing hypertension awareness as part of a blood donation screening is not only needed but also useful as a public health measure.